STUDI KASUS : OBSERVASI PERSALINAN SEBAGAI STRATEGI PENCEGAHAN KOMPLIKASI - Achmad, Ismiyanti; Hermanses, Sitti Suharni (Jurnal Kebidanan, 2025)
This case study aims to describe the comprehensive observation of labor progress in a multiparous woman, Ny. D, who underwent spontaneous vaginal delivery with oxytocin induction due to postdate pregnancy. Labor observation was carried out intensively using systematic monitoring of uterine contractions, cervical dilation, fetal heart rate, maternal vital signs, and partograph recording. The case presentation includes detailed findings during the latent and active phases, decision-making during induction titration, and management according to safe delivery standards. Discussion highlights the alignment and variations between case management and current evidence-based guidelines, particularly regarding the timing of induction, assessment of fetal well-being, and documentation accuracy. The conclusion emphasizes that structured and continuous labor observation significantly contributes to safe maternal and neonatal outcomes. Recommendations include optimizing decision-making protocols, strengthening partograph utilization, and enhancing clinical readiness in monitoring induced labor